A study of incidence and pattern of coronary artery anomalies in Western Rajasthan, India - Lingaraju, Satish; Maurya, Rakesh Kumar; Sanghvi, Sanjeev (International Journal of Research in Medical Sciences, 2017)
Background: Coronary artery anomalies (CAAs) are a diverse group of congenital disorders whose manifestations and pathophysiological mechanisms are highly variable. Among patients undergoing coronary angiography, the incidence depends on the population studied and the criteria used to define an anomaly. This is the first ever study conducted in western Rajasthan to detect the incidence and pattern of coronary anomalies. Methods: We retrospectively studied 8500 coronary angiographies (CAG) done in the institution over a period of 12 years from 2004 to 2015 for detection of incidence and pattern of coronary anomalies. Patients with ischemic heart disease and valvular heart disease who underwent CAG were included in the study. Results: Out of the 8500 angiograms screened a total of 108 coronary anomalies were detected (incidence of 1.27%). Anomalies of origin and course was the most common anomaly (106 out of 108 patients) followed by anomalies of coronary termination (fistulas) which was seen in just two patients. Most common anomaly was absent left main artery with separate origin of the left anterior descending (LAD) artery and left circumflex artery (LCx) (n=36, 33.3%), followed closely by anomalous origin of right coronary artery (RCA) from left sinus (n=34, 31.48%). Anomalous origin of LCx from right sinus/ RCA was the third most common anomaly (n=22, 20.37%). Other rare anomalies include anomalous origin of left coronary artery from right coronary sinus (n=6, 5.55%), RCA from posterior sinus (n=4, 3.7%). Single coronary artery, LAD from RCA and coronary artery fistula were seen in two patients each (n=2, 1.85%). Conclusions: In present study though the total incidence of coronary anomalies was similar to that in other studies, the pattern of coronary anomalies was slightly different from that reported from different parts of the world.